Graphene Oxide as a Platform for Copper Pentacyanonitrosylferrate Nanoparticles and their Behavior in the Electro-oxidation of N-Acetylcysteine - Maraldi, Vitor Alexandre [UNESP]; Colmenares, Yormary Nathaly; Pereira Barbosa, Priscila Fernanda [UNESP]; Mastelaro, Valmor; Ribeiro do Carmo, Devaney [UNESP] (Wiley-Blackwell, 2020)
This work describes the preparation of graphene oxide by the Modified Hummers Method and the chemical modification of its surface with nanoparticles of copper pentacyanonitrosylferrate(III) (GOCuNP). The materials obtained were characterized by Raman spectroscopy, x-ray photoelectron spectroscopy and transmission electron microscopy. The GOCuNP was characterized by cyclic voltammetry using a graphite paste electrode that presented electrocatalytic response for N-acetylcysteine with detection limit of 2.97x10(-5) mol L(-1)at concentration range of 3.00x10(-5)to 6.00x10(-3) mol L(-1)of N-acetylcysteine. By this way, the bimetallic complex formed is included in the list of materials obtained as potential candidates for the construction of electrochemical sensors for N-acetylcysteine detection.
Keywords: Graphene Oxide; Copper Pentacyanonitrosylferrate(III); Nanoparticles; Cyclic Voltammetry; Catalytic Electro-oxidation